Hubungan Partisipasi Siswa dalam Kegiatan Ekstrakurikuler Pramuka dengan Sikap Percaya Diri Siswa SDN 71 Kota Bengkulu - Suraina, Elta; Yuliantini, Nani; Susanti, Atika (JURIDIKDAS, 2024)
This research aims to determine the relationship between student participation in scout extracurricular activities and the self-confidence of students at SDN 71 Bengkulu City. This type of research is quantitative research using quantitative correlational research methods. The population in this study were class IV students at SDN 71 Bengkulu City who took part in scout extracurriculars. In this study, sampling used a total sampling technique, namely the entire population was sampled, the sample in this study was 32 people. The research instrument uses a closed questionnaire using a Likert scale. The data analysis used is a prerequisite test using the normality test, correlation analysis, namely the variable significance test and the coefficient of determination test. The results of this research show that there is a significant relationship between student participation in scout extracurricular activities and self- confidence. These results are proven by the sig* (2-tailed) value of 0.002 with a Pearson correlation value of 0.534, a sign that the regression coefficient is positive. The variable size of student participation in scout extracurricular activities on the self-confidence variable is 26.8%. This means that it can be concluded that there is a relationship between student participation in scout extracurricular activities and the self-confident attitude of students at SDN 71 Bengkulu City.